Web-based Cashier Information System for Car and Motorcycle Washing Company - Abednego Wijaya Adiwibowo; Agus Cahyo Nugroho; T. Bernadinus Harnadi (Soegijapranata Catholic University, 2026)
The motorbike and car wash company is one of the SMEs in the service sector. The company needs recording their transactions better. Previously, the company used a recording system that is less efficient in manually written on paper, so that they have difficulty in calculating revenue and transaction amounts. Their system also has a risk of losing transaction records and less secure. Therefore, this system was created using the RAD (Rapid Application Development) method. This system was built using Laravel and Filament to further shorten production time. The research results a cashier information system. With this system, the company can record the necessary data and transactions. The transactions recorded in the system are automatically stored in the database. This system was tested by company owner and their admin using interview model. The interview results stated that the admin and owner felt a positive impact after implementing this cashier information system. Admins feel safety when record customer data including transactions because the data is stored safely in the database. The company owner can also analyze revenue through the number of transactions so that he can determine a more accurate business strategy.